Synthesis and characterization of P δ-layer in SiO2 by monolayer doping. (20th January 2016) - Arduca, Elisa; Mastromatteo, Massimo; Salvador, Davide De; Seguini, Gabriele; Lenardi, Cristina; Napolitani, Enrico; Perego, Michele
Abstract: Achieving the required control of dopant distribution and selectivity for nanostructured semiconducting building block is a key issue for a large variety of applications. A promising strategy is monolayer doping (MLD), which consists in the creation of a well-ordered monolayer of dopant-containing molecules bonded to the surface of the substrate. In this work, we synthesize a P δ −layer embedded in a SiO2 matrix by MLD. Using a multi-technique approach based on time of flight secondary ion mass spectrometry (ToF-SIMS) and Rutherford backscattering spectrometry (RBS) analyses, we characterize the tuning of P dose as a function of the processing time and temperature. We found the proper conditions for a full grafting of the molecules, reaching a maximal dose of 8.3 × 10 14 atoms/cm 2 . Moreover, using 1D rate equation model, we model P diffusion in SiO2 after annealing and we extract a P diffusivity in SiO2 of 1.5 × 10 17 cm 2 s −1 .